Rancang Bangun Jaringan Dengan Bandwidth Management Menggunakan Firewall - Az-zahra, Rizka Namira Nur; Apra, Dhia Fauziah; Nurjanah, Esa; Maulidia, Dea; Fauzi, Abdurahman (Jurnal Teknologi Informasi (JUTECH), 2021)
This research has a case study in one of the cafes in the city of Bandung, namely 150 Coffee and Garden. This cafe is a gathering place for people who also provides internet or wifi networks that can be accessed by all visitors. The internet network will be connected to the server so it is necessary to apply a filter to restrict visitor access. In addition, to maintain the stability of internet access requires a bandwidth management. To solve this problem, this research uses a firewall feature using Mikrotik RB941 as access security. The test results show that the system can run well. The system can provide different bandwidth for staff, employees and visitors. Also the application of a firewall can block sites that network administrators want.